Comparative Bioactivities Study of Five Dietary Plants Used in Malaysia - Wong, F.C.; Yap, Y.V.; Chai, T.T. (Asian Journal of Chemistry, 2014)
The purpose of this study was to determine the bioactivities and phytochemical contents of five food plants used in Malaysia. Radical scavenging activities were determined based on measurements of DPPH at 517 nm. Total phenolic and hydroxycinnamic acid contents were determined using spectrophotometric methods. Antibacterial activities were measured using Kirby-Bauer susceptibility test. Our results suggested that S. torvum is an ideal source of radical scavengers and total phenolics, while G. atroviridis could potentially be exploited to yield broad-range antibacterial therapeutic agents.